Coronal plane fractures of the distal humerus involving the capitellum and trochlea treated with open reduction internal fixation - Bilsel, Kerem; BİLSEL, İSMAIL KEREM; Atalar, Ata Can; ERDIL, Mehmet; Elmadag, Mehmet; ELMADAĞ, NUH MEHMET; SEN, Cengiz; Demirhan, Mehmet (My University, 2013)
Coronal plane fractures of the distal humerus involving the capitellum and trochlea are rare. Treatments have evolved from closed reduction to open reduction and internal fixation (ORIF) to achieve a stable joint that allows early mobilization.